Dukungan Keluarga dan PMO yang Mempengaruhi Kepatuhan Pasien TB dalam Mengonsumsi Obat - Willi Willem; Nova Mega Rukmana; Nur Sefa Arief Hermawan; Indah Rinfilia (Jurnal Sains & Kesehatan, 2023)
The low rate of recovery coverage and success of tuberculosis is a bad risk and is a serious problem for public health status.The success of tuberculosis is greatly influenced by obedience to treatment.In the town of the king's city., from the existing data of 30 puskemmas, no one has reached target 100 % success, treatment success rate is only 79.9 %.The success of tuberculosis is greatly influenced by obedience to treatment.The purpose of research to find out the relationship of family support and the role of pmo with the patient's obedience in ingesting drugs.Kind of categorical research, cross sectional design.Sample number 33 people.Data collecting method by interviewing using questionnaires.Spamling consecutive sampling technique.Research results, say there's a family support connection p-value 0.038, and pmo role with p-value 0.010